The Lord's Prayer - Palmer, George Herbert (Harvard theological review, 1920)
In both the Old Testament and the New there is a climactic point, a passage, I mean, which so epitomizes all the teaching of that section of our Bible that we should be eager to save it were all else to be destroyed. In the Old Testament it is the Ten Commandments, which form a foundation for civil society. Society would go to pieces were not the Ten Commandments understood and usually obeyed. In the New Testament it is the Lord's Prayer, which lays foundations for the harmonious inner life as the Ten Commandments do for the outer. Here speaks the aspiring spirit to its Maker. This is the love-song of the Christian world. Few precepts of our Master, I suppose, have been more widely observed than that we are to “pray in this manner.” For most of us that day would lack something in which the Lord's Prayer had not been repeated. It fits all circumstances. It is the chant of the saint in his most exultant moments, his refuge and solace when most depressed. The poor sinner, who through walking in the ways of vice has almost lost the power of aspiration and can no longer formulate for himself his better desires, finds in these sacred phrases his appropriate utterance.